Integrasi kurikulum Merdeka Dan Teknologi Pada Pembelajaran Pancasila Di sekolah dasar - Sha’af, Mohammad Adnan (Maliki Interdisciplinary Journal, 2025)
With the development of technology and curriculum in the current era, learning media plays an important role in helping the teaching and learning process, so that an educator can utilize learning media that is starting to develop to be used as a tool in delivering material so that the teaching and learning process is easier to do. The use of audio-visual-based learning media is very much needed in the current era because we see today’s students who are attached to gadgets as their current life. For that, teachers can see the condition or characteristics of students and adjust the use of learning media during the teaching and learning process. The creation or application of audio-visual learning media in this PKN lesson can prove that students are active in their learning.